PENINGKATAN PRESTASI BELAJAR SISWA DENGAN METODE DISKUSI PADA MATERI SISTEM PEMERINTAHAN DESA DAN KECAMATAN - Suwarmi Suwarmi (MEDIA DIDAKTIKA, 2016)
The purpose would be achieved by the researcher in instructional improvement activities are as follows: (1) Analyze the implementation of discussion method in learning Civics primarily on the material of Village and District Governance System. (2) Describe the discussion method in teaching civics primarily on the material of Village and District Governance System (3) analyze the effect of the implementation of discussion method on the material of Village and District Governance System in an effort to improve the students’ learning outcomes. From the results of the research showed that learning using the discussion method can be concluded that in each cycles there was an increase, where the average value of the results of the evaluation of the pre-cycle, the first cycle and the second cycle subjects Civics at fourth grade in the first semester of the state elementary school of Paciran, district Paciran, Lamongan with material of Village and District Governance System. Before the improvement of learning (pre-cycle) the average value of 57.3. In the first cycle the average value 68.5 and the second cycle the average value 81.8. The increase in the average value of the first cycle to the second cycle was 13.9. It could be concluded that the learning on the material of Village and District Governance System using discussion method successfully with very satisfactory results.